2020
DOI: 10.1007/s12011-020-02358-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Approach and Neutron Activation Analysis for Determining Essential and Toxic Elements in Two Kinds of Algerian Artemisia Plant

Abstract: In this study, two kinds of Artemisia plant, Artemisia campestris L. and Artemisia herba-alba Asso., collected from different locations in Djelfa province, Algeria, were subjected to an instrumental neutron activation analysis (INAA) in order to determine their essential and toxic elements for the first time. The obtained results for both types revealed the existence of twenty-one elements, namely, As,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…A perusal of data in Table 1 shows that this plant is rich in some essential elements like Na, K, Ca, Mg, P, and S, from which the electrolytic elements of Na and K can be highlighted because they are responsible for maintaining healthy fluid balance inside and outside cells (Begaa & Messaoudi, 2019; Begaa et al., 2020; Garg et al., 2007). The concentrations of Na and K are found in 2.034 and 11.51 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A perusal of data in Table 1 shows that this plant is rich in some essential elements like Na, K, Ca, Mg, P, and S, from which the electrolytic elements of Na and K can be highlighted because they are responsible for maintaining healthy fluid balance inside and outside cells (Begaa & Messaoudi, 2019; Begaa et al., 2020; Garg et al., 2007). The concentrations of Na and K are found in 2.034 and 11.51 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It can be expressed in natural or ratio units. The statistics distinguish two groups of variability measures [ 6 , 36 ]—absolute measures of variability (nominated) and relative measures of variability—and they depend on the average value of the studied feature. The relative measures of variability include the coefficient of variation.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants and their medicinal properties have been widely studied, especially in developing countries [ 1 , 2 , 3 , 4 ]. The World Health Organization has acknowledged the importance of medicinal plants, along with traditional medicine, which has received global attention [ 5 , 6 ]. In many countries, such as Algeria, there is a search for alternative medicine, including traditional herbal treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported that human health needs several elements that are considered micronutrients, including potassium and sodium, where both electrolytic elements K and Na are responsible for maintaining a normal fluid balance inside and outside cells [51][52][53]. Moreover, it is recommended that the concentration levels of K be major and Na be minor; in this study, the concentrations of K and Na were found to be 24,564 and 12,442 mg/kg, respectively.…”
Section: Mineral Elemental Analysis Mineral Elemental Analysismentioning
confidence: 54%